Reproductive Risk Factors Associated with Female Infertility in Sonepat District of Haryana: A Community Based Cross-Sectional Study - Deepika Kataria; Babita Rani; Anita Punia; S. K. Jha; M. Narendran; Jagmohan Singh (Journal of Human Reproductive Sciences)
Background: Infertility is a disease of the male or female reproductive system defined by the failure to achieve a pregnancy after 12 months or more of regular unprotected sexual intercourse. Aims: The aim of this study was to estimate the prevalence of infertility and its association with reproductive risk factors amongst women of reproductive age group (18–49 years) in district Sonepat, Haryana. Settings and Design: This observational community-based cross-sectional study was conducted amongst 444 reproductive age group (18–49 years) women residing in district Sonepat, from August 2021 to May 2022. Materials and Methods: A simple random sampling technique was used to select the study subjects. After taking written informed consent, all the participants were interviewed using a pre-designed, pre-tested semi-structured questionnaire for desired information. Statistical Analysis Used: Mean and standard deviation (SD) were calculated for quantitative data. Percentages and proportions were calculated for qualitative data. Results: Out of 444 study population, majority of women were fertile (88.7%), while 6.3% of women were secondary infertile and 5% of women were primary infertile. Most women were aged between 30 and 39 years. The difference of occurrence of infertility in relation to genital discharge (P = 0.049), genital ulcer/sores (P ≤ 0.001), groin swelling (P ≤ 0.001), warts (P = 0.015), menstrual cycle duration (P ≤ 0.001) and menstrual flow amount (P = 0.048) was statistically significant. The mean age of menarche for the female with infertility was 14.34 years (standard deviation = 1.40). Conclusion: Almost all of the symptoms of sexually transmitted infection/reproductive tract infection were high amongst infertile females. Awareness generation about the preventable risk factors and provision of infertility care services at primary healthcare facilities will be of use in addressing infertility in Sonepat.